Socio-demographic inequalities in the prevalence, diagnosis and management of hypertension in India: analysis of nationally-representative survey data. - Kath A Moser; Sutapa Agrawal; George Davey Smith; Shah Ebrahim (PLoS ONE)
Background Hypertension is a major contributing factor to the current epidemic of cardiovascular disease in India. Small studies suggest high, and increasing, prevalence especially in urban areas, with poor detection and management, but national data has been lacking. The aim of the current study was to use nationally-representative survey data to examine socio-demographic inequalities in the prevalence, diagnosis and management of hypertension in Indian adults. Methods Using data on self-reported diagnosis and treatment, and blood pressure measurement, collected from 12,198 respondents aged 18+ in the 2007 WHO Study on Global Ageing and Adult Health in India, factors associated with prevalence, diagnosis and treatment of hypertension were investigated. Results 22% men and 26% women had hypertension; prevalence increased steeply with body mass index (<18.5 kg/m(2): 18% men, 21% women; 25-29.9 kg/m(2): 35% men, 35% women), was higher in the least poor vs. poorest (men: odds ratio (95%CI) 1.82 (1.20 to 2.76); women: 1.40 (1.08 to 1.81)), urban vs. rural men (1.64 (1.19 to 2.25)), and men recently vs. never using alcohol (1.96 (1.40 to 2.76)). Over half the hypertension in women, and 70% in men, was undetected with particularly poor detection rates in young urban men, and in poorer households. Two-thirds of men and women with detected hypertension were treated. Two-thirds of women treated had their hypertension controlled, irrespective of urban/rural setting or wealth. Adequate blood pressure control was sub-optimal in urban men. Conclusion Hypertension is very common in India, even among underweight adults and those of lower socioeconomic position. Improved detection is needed to reduce the burden of disease attributable to hypertension. Levels of treatment and control are relatively good, particularly in women, although urban men require more careful attention.